Antecedents Affecting Teacher Performance At Smpit Annur Cikarang Timur - Tomy Johan Fauzi; Abdul Ghafar (Jurnal Indonesia Sosial Teknologi, 2023)
This study investigates the influence of the principal's leadership style and school climate on teacher performance at SMPIT Annur Cikarang Timur. This study used a multiple linear regression analysis method to analyze the collected data. The results of this study show that simultaneously, the principal's leadership style and school climate have a positive and significant effect on teacher performance. The simultaneous hypothesis test confirms that the principal's leadership style and school climate contribute significantly to teacher performance at SMPIT Annur Cikarang Timur. These results indicate that the role of the headmaster in developing an effective leadership style and creating a conducive school climate is critical in improving teacher performance. In addition, the hypothesis test partially showed that each of the variables, namely the principal's leadership style and school climate, positively and significantly influence individual teacher performance. Thus, the results of this study make an essential contribution to improving teacher performance and school management. The practical implications of this research are the importance of developing effective principal leadership and creating a conducive school climate as factors that can improve teacher motivation and performance. This research can also be a foundation for developing better school management strategies at SMPIT Annur Cikarang Timur and similar educational institutions